Ideological and political education as a mechanism of cultural identity formation: a systematic review of contemporary chinese higher education - Chen, Wei; Fee, Lee Yok; Ratna Roshida, Binti Ab Razak; Majid, Arfah Binti Ab (Dr. Yashwant Research Labs Pvt. Ltd., 2026)
Through a systematic review approach, this study explores the mechanism and role of ideological and political education in the formation of cultural identity among Chinese college students. Through a comprehensive analysis of relevant academic literature published between 2014 and 2024, this study reveals how ideological and political education systematically shapes the cultural identity of college students through multidimensional mechanisms such as institutionalized structure, curriculum integration, cultural practice and values cultivation. The study finds that ideological and political education in contemporary Chinese higher education has developed into a comprehensive institutional system that promotes students' deep internalization of Chinese culture, socialist core values and national identity through a variety of channels, including formal teaching, extracurricular activities, campus culture construction and digital platforms. This study identifies key challenges in the implementation of ideological and political education, including the tendency of formalism, insufficient student participation, and the disconnection between theory and practice, and proposes strategies to enhance the effectiveness of education. The study is of great theoretical significance in understanding the unique path of cultural identity formation in Chinese higher education, and provides a reference perspective for identity education in other multicultural education contexts.